2021
DOI: 10.1253/circrep.cr-21-0067
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type Transthyretin Amyloidosis in Female Patients ― Consideration of Sex Differences ―

Abstract: Background: With recent advances in non-invasive diagnostic tools, some studies indicate that wild-type transthyretin amyloidosis (ATTRwt) may be more common in females than previously reported. However, the clinical characteristics of female ATTRwt patients have not been determined. Methods and Results:Of the 78 consecutive patients with ATTRwt in our cohort, 14 (17.9 %) were female. Compared with male patients, female ATTRwt patients had smaller left ventricular (LV) wall thicknesses (ventricular septum thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…Ochi et al demonstrated that the prevalence of wild-type transthyretin amyloidosis in female patients was higher than in previous reports. 1 Female patients tended to have heart failure symptoms despite mild cardiac hypertrophy and preserved ejection fraction. Several concerns have been raised.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Ochi et al demonstrated that the prevalence of wild-type transthyretin amyloidosis in female patients was higher than in previous reports. 1 Female patients tended to have heart failure symptoms despite mild cardiac hypertrophy and preserved ejection fraction. Several concerns have been raised.…”
mentioning
confidence: 99%
“…In the study of Ochi et al, the thickness of the left ventricular wall was less in female than male patients. 1 Thus, it may be more challenging to suspect cardiac amyloidosis in daily clinical practice among female patients. Were there any differences in the signs and chief complaints between female and male patients?…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We are grateful to Drs. Imamura and Nakamura for their interest in and comments on our study, 1 and for highlighting some issues regarding the diagnostic and therapeutic strategies for female patients with wild-type transthyretin amyloidosis (ATTRwt) in an aged Japanese community.…”
mentioning
confidence: 99%